2000
DOI: 10.1562/0031-8655(2000)072<0575:iopaiw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Photolyase Activity in Wood Frog (Rana sylvatica) Embryos¶

Abstract: Rising ultraviolet-B (UVB, 280-320 nm) radiation has been proposed as a factor which may explain nonnormal amphibian population declines. Accordingly research has been directed toward estimating the photolyase activity of several amphibian species in order to predict a species' resilience to UV damage. Unfortunately, in spite of published research which demonstrated that the activity of one of the principal photorepair enzymes, photolyase, can be induced, these estimates did not address the potential for in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…1994; Malloy et al . 1997; Smith, Kapron & Berrill 2000). Even under optimal conditions (25 °C, WL + UV‐A), the CPD repair rates displayed by G. magellanica leaves appeared to be modest in comparison with published repair kinetics for other species (Pang & Hays 1991; Quaite et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1994; Malloy et al . 1997; Smith, Kapron & Berrill 2000). Even under optimal conditions (25 °C, WL + UV‐A), the CPD repair rates displayed by G. magellanica leaves appeared to be modest in comparison with published repair kinetics for other species (Pang & Hays 1991; Quaite et al .…”
Section: Resultsmentioning
confidence: 99%
“…Although no comparative surveys are available in the case of terrestrial plants, variation appears to exist in DNA repair capacity among animal species that live in contrasting UV environments (Blaustein et al 1994;Malloy et al 1997;Smith, Kapron & Berrill 2000). Even under optimal conditions (25 °C, WL + UV-A), the CPD repair rates displayed by G. magellanica leaves appeared to be modest in comparison with published repair kinetics for other species (Pang & Hays 1991;Quaite et al 1994; Sutherland et al and irradiation (open symbols: WL + UV-A; closed symbols: darkness).…”
Section: Environmental Regulation Of Dna Repair Capacitymentioning
confidence: 99%
“…The assumption that melanin could have a major role against deleterious effects caused by UVB radiation on R. (Bufo) arenarum embryos is in line with the study reported by Perotti and Diéguez [9] in which the photoprotection against UVB radiation in three amphibian species was associated to the melanin content of the embryo. On the other hand, photolyase, one of the principal photo repair enzymes induced by UVB irradiation and antioxidant molecules such as catalase, superoxide dismutase, and glutathion peroxidase, could also contribute to the protection of UVB‐irradiated embryos [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of photolyase expression, the response of organisms to UV‐R exposure and resulting DNA damage is species specific. Whereas photolyase is often constitutively expressed independent of UV‐R exposure (25–27), expression of photolyase in Rana sylvatica embryos has been positively correlated with UVB dose (27), and in Carassius auratus , by exposure to visible light (26). The present study suggests that while there is also constitutive photolyase expression in Sterechinus embryos, expression does vary with depth and UV‐R dose.…”
Section: Discussionmentioning
confidence: 99%